Molecular epidemiological investigation of piroplasms carried by pet cats and dogs in an animal hospital in Guiyang, China - Wu, Shengchun; Meng, Jiao; Yu, Fuxun; Zhou, Caomin; Yang, Bin; Chen, Xingxing; Yang, Guanghong; Sun, Yi; Cao, Wuchun; Jiang, Jiafu; Wu, Jiahong; Zhan, Lin (Frontiers in Microbiology, 2023)
Piroplasmosis is a zoonotic disease mainly caused by the Babesia and Theileria parasites.Piroplasmosis is often a subclinical infection in dogs and cats that is difficult to detect and is often suspected when clinical signs such as anaemia are present. It has been reported to be prevalent in China. However, molecular evidence of the disease has not been reported in pet dogs and cats in Guiyang. In this study, we collected 307 anticoagulated blood samples from an animal hospital in the Wudang District of Guiyang during the period March 2021 to November 2021 and extracted DNA from the samples. The 18S rDNA gene was amplified using PCR, and the positive amplification product was sequenced. The sequences were then analyzed for homology and phylogeny. Of the 307 samples collected, 164 were feline and 143 were canine, with a total of 23 amplifying a target band of approximately 400 bp. The percentage of positives of piroplasms infection in pet cats was 4.27% (7/164), with the pathogens being T. uilenbergi (3) and T. luwenshuni (4). One Colpodella sp. and two undetermined species were also detected in the cat samples. The percentage of positives of piroplasms infection in pet dogs was 7.69% (11/143), with the pathogen being T. uilenbergi (11).One Colpodella sp. was also detected in the dog samples. The results confirmed that T. uilenbergi and T. luwenshuni are prevalent in pet cats and dogs in this area. In addition, the study found a rare zoonotic pathogen, Colpodella sp., in cats and dogs. Therefore, this study is expected to serve as a valuable reference for decision-making regarding animal health management and public health work.